Women's experience of induction of labor: A mixed methods study - Henderson, J; Redshaw, M (2013)
Objective To investigate women's experience of induction of labor. Design Mixed methods study. Setting English maternity units. Sample Women who gave birth in a two-week period in late 2009, excluding women aged less than 16 years and women whose baby had died. Methods This study involved secondary analysis of data from questionnaires relating to care in childbirth. Women's experience of induction of labor was compared with that of women who had spontaneous labor by analysis of responses to structured survey questions. Responses to open questions relating to induction were analysed qualitatively. Main outcome measures Satisfaction with care, mode of delivery, experience of induction of labor. Results The response rate to the survey was 55.1% representing 5333 women, 20% of whom were induced. Nulliparous women, those with long-term health problems, or specific pregnancy-related problems were significantly more likely to be induced. Women who were induced were generally less satisfied with aspects of their care and significantly less likely to have a normal delivery. In the qualitative analysis the main themes that emerged concerned delay, staff shortages, neglect, pain and anxiety in relation to getting the induction started and once it was underway; and in relation to failed induction, the main themes were plans not being followed, wasted effort and pain, and feeling let down and disappointed. Conclusions Women having an induction were generally less satisfied with their care, suggesting the need for a focused service for these women to address their additional needs. © 2013 Nordic Federation of Societies of Obstetrics and Gynecology.